Pemoline in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The effects of pemoline (Cylert) in 28 children with attention deficit disorder (ADD), 23 with and 5 without hyperactivity, were evaluated for dose-response, timing of response after ingestion, and duration of effect, in a double-blind, placebo-controlled, crossover study at the Child Development Clinic of the Department of Neurology, Hospital for Sick Children, Toronto, Canada.